E-learning in the coronavirus’s period from the perspective of students - Lekiqi, Bislim; Rexhepi, Aziz; Sahiti, Albina (Technium Social Sciences Journal, 2021)
The Coronavirus epidemic in Kosovo is having consequences in all spheres of life. This reflection is especially noticeable in teaching and learning, especially at the university level, moving from the classical (traditional) form of teaching fully or partially to e-learning. The necessity of such a rapid transformation and the need to achieve the objectives of studies are being assessed by students in different ways. The subject of this research is how students evaluate this rapid transformation from traditional teaching and learning to e-learning, which was conducted in December 2020. 551 Kosovar Bachelor and Master students participated in the research. The research was done through a survey. The analysis of the results, their comparison leads us to the conclusions and recommendations, information which could serve the university institutions and state decision-making structures for the orientation of educational policies in a new era of digitalization, where e-learning is becoming a necessity even in developing countries. Where work enables us to understand that developments in the field of education, imposed by the epidemic, will be one of the forms of teaching and learning in the future and that for this we must all prepare as individuals and as a society in general.